Project-Based Learning (PJBL) Berbasis Strategi Motivasional Attention, Relevance, Confidence, Satisfaction (ARCS) dan Pengaruhnya terhadap Motivasi dan Sikap Ilmiah Biologi pada Materi Perubahan Lingkungan yang telah Dieksperimenkan di Kelas X MIPA SMA Negeri 11 Pinrang - Ainurridho, Muhammad; Bahri, Arsad; Muhiddin. P, Muhiddin. P (Universitas Negeri Makassar, 2021)
Abstract. This study aims to determine the effect of the Project-Based Learning learning model based on ARCS motivational strategies on motivation and students scientific attitude on the environmental change in 10th grade of SMAN 11 Pinrang. This type of research is quasi-experimental research involving two groups in which one acts as an experimental group and the other as a control group with the research design Matching pretest-postest comparison group design. The sample in this study were students of class X EXACT 2 as an experimental class and class X EXACT 1 as a control class obtained using random sampling techniques by taking cognitive scores from the previous semester and looking at their equivalence with a significance value of 0.275 with a class conclusion conducted an equivalent study in terms of cognition. The type of research instruments used were the Motivation and Scientific Attitudes questionnaire. The learning outcomes test in the form of multiple choice tests is used as supporting data to prove the correlation or relationship between students' motivation with the learning outcomes they have obtained. Descriptive statistics are used to describe interests and learning outcomes while inferential statistics to test the research hypotheses carried out by covariance analysis. The results showed that (1) there was an influence on the use of PJBL based on ARCS motivational strategies on the students motivation of SMAN 11 Pinrang (2) there was an influence on the use of PJBL based on ARCS motivational strategies on the scientific attitude of SMAN 11 Pinrang.Keywords: PJBL, ARCS motivational strategy, motivation questionnaire, scientific attitude questionnaire